PENGARUH KEJELASAN PELAYANAN, KEDISIPLINAN PETUGAS PELAYANAN, KECEPATAN PELAYANAN DAN INFRASTRUKTUR TERHADAP KEPUASAN MASYARAKAT - Hermanto Hermanto (UNEJ e-Proceeding)
This research aims to influence the clarify of service, disciplined services officers, speed of service, and infrastructure on community satisfaction at Health Center of Leces Probolinggo. The population of this research are all patients or people who were visiting a health service in health centers of Leces and sampling method used purposive sampling. The data collection method documentation, and questionnaires. Data were analyzed using descriptive analysis and multiple linear regression analysis. Calculation of multiple linear regression analysis regression equation: Y = 2.678 + 0.286 X1 + 0.430 X2 + 0.298 X3 + 0.095 X4, meaning there are no community satisfaction by 2.678 points without the involvement of the four variables in this study. While the amount of influence of the four variables to satisfaction of the community amounted to 93.3% and the remaining 6.7% is influenced by other factors. From the analysis, the discipline of service personnel more significantly to the satisfaction of the people than the clarity of service, speed of service personnel and infrastructure. Based on the research results, infrstruktur have the lowest contribution for that management should consider the availability of facilities and infrastructure to ensure the comfort and satisfaction of the people at the health center Leces Probolinggo.